Dynamics of SAS-I mediated H4 K16 acetylation during DNA replication in yeast. - Mark Boltengagen (Public Library of Science (PLoS), 2021)
The acetylation of H4 lysine 16 (H4 K16Ac) in Saccharomyces cerevisiae counteracts the binding of the heterochromatin complex SIR to chromatin and inhibits gene silencing. Contrary to other histone acetylation marks, the H4 K16Ac level is high on genes with low transcription, whereas highly transcribed genes show low H4 K16Ac. Approximately 60% of cellular H4 K16Ac in S. cerevisiae is provided by the SAS-I complex, which consists of the MYST-family acetyltransferase Sas2, Sas4 and Sas5. The absence of SAS-I causes inappropriate spreading of the SIR complex and gene silencing in subtelomeric regions. Here, we investigated the genome-wide dynamics of SAS-I dependent H4 K16Ac during DNA replication. Replication is highly disruptive to chromatin and histone marks, since histones are removed to allow progression of the replication fork, and chromatin is reformed with old and new histones after fork passage. We found that H4 K16Ac appears in chromatin immediately upon replication. Importantly, this increase depends on the presence of functional SAS-I complex. Moreover, the appearance of H4 K16Ac is delayed in genes that are strongly transcribed. This indicates that transcription counteracts SAS-I-mediated H4 K16 acetylation, thus "sculpting" histone modification marks at the time of replication. We furthermore investigated which acetyltransferase acts redundantly with SAS-I to acetylate H4 K16Ac. esa1Δ sds3Δ cells, which were also sas2Δ sir3Δ in order to maintain viability, contained no detectable H4 K16Ac, showing that Esa1 and Sas2 are redundant for cellular H4 K16 acetylation. Furthermore, esa1Δ sds3Δ sas2Δ sir3Δ showed a more pronounced growth defect compared to the already defective esa1Δ sds3Δ sir3Δ. This indicates that SAS-I has cellular functions beyond preventing the spreading of heterochromatin.